EFEKTIVITAS BALAI BESAR PENGAWAS OBAT DAN MAKANAN TERHADAP PENERTIBAN PELAKU USAHA KOSMETIK ILEGAL DI KOTA PADANG - Aynainil Mardiyah; Aldri Frinaldi (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2019)
The higher the cosmetic needs, the easier the cosmetic circulation can be found. The purpose of this study was to find out how the effectiveness of Balai Besar Pengawas Obat dan Makanan on the control of cosmetic businesses in the city of Padang. Control is done to increase legal awareness of business actors and social control. The results of this study indicate that, first, there has not been a growing adherence of business actors to existing laws, so that illegal cosmetics are still marketed. Even though guidance or socialization has been carried out, but that is not enough to raise awareness of business actors on existing laws. Second, how social control is carried out by Balai Besar Pengawas Obat dan Makanan on business so that illegal cosmetics circulation has not reached its goals and objectives, due to socialization which has not been carried out thoroughly and because of legal sanctions that have not been firmly implemented.